1992
DOI: 10.1093/geronj/47.6.b202
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Restriction Alters Characteristics of Glucose Fuel Use

Abstract: A longitudinal study of plasma glucose and insulin concentrations in ad libitum fed and dietary restricted male F344 rats was carried out. The life span diurnal pattern of plasma glucose concentration was such that through most of the day dietary restricted rats have significantly lower plasma glucose levels than ad libitum fed rats. Throughout the life span, dietary restricted rats maintain mean 24-hour plasma glucose concentrations about 15% below those of ad libitum fed rats. Plasma insulin levels are maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
149
1
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(172 citation statements)
references
References 0 publications
21
149
1
1
Order By: Relevance
“…the opposite of the effect of elevated glucose. This similarity further supports that in mammals effects of dietary restriction on life span are mediated by a reduction in exposure to glucose [1], as is the case in yeast [3].…”
Section: Dietary Restriction Reduces Glycolysis and Increases Oxidatisupporting
confidence: 81%
See 1 more Smart Citation
“…the opposite of the effect of elevated glucose. This similarity further supports that in mammals effects of dietary restriction on life span are mediated by a reduction in exposure to glucose [1], as is the case in yeast [3].…”
Section: Dietary Restriction Reduces Glycolysis and Increases Oxidatisupporting
confidence: 81%
“…This hypothetical common mechanism does not appear to require a reduction in metabolic rate, since neither the clk-1 mutation [35,36] nor dietary restriction [41,42] reduce mass-specific oxygen consumption in C. elegans. Similarly, the mechanism by which dietary restriction increases life span in yeast [3] and mammals [1,43] appears not to require a reduction in mass-specific oxygen consumption. On the other hand, several lines of evidence suggest that a final common mechanism by which life-extending mutations [44,45] and dietary restriction [46,47] increase life span entails reducing oxidative damage.…”
Section: Dietary Restriction May Increase Life Span By Reducing Oxidamentioning
confidence: 97%
“…both these parameters are increased with IF compared to CR (Dunn et al, 1997;Anson et al, 2003). A longitudinal study on male rats (Masoro et al, 1992) demonstrated that CR decreased the mean 24-h plasma glucose concentration by about 15 mg/dl and the insulin concentration by about 50%. CR regime animals utilized glucose at the same rate as did the rats fed ad libitum, despite the lower plasma glucose and markedly lower plasma insulin levels.…”
Section: Glucose/insulin Signalingmentioning
confidence: 99%
“…Long-term calorie restriction (CR) without malnutrition, the most robust intervention to extend average and maximal lifespan in rodents (Fontana & Klein 2007), improves insulin sensitivity, reduces fasting glucose, and insulin concentration in rodents and monkeys (Masoro et al 1992;Kemnitz et al 1994;Lane et al 1995;Cefalu et al 1997;Barzilai et al 1998;Gresl et al 2001), and in some (Lane et al 1995;Masoro et al 1992), but not all cases (Kalant et al 1988;Bodkin et al 1995;Cefalu et al 1997;Barzilai et al 1998), improves glucose disposal compared with ad libitum fed animals. It has been proposed that improved insulin sensitivity, and reduced plasma glucose with less glycation of macromolecules, play a major role in the life-extending effect of CR (Cerami 1985).…”
Section: Introductionmentioning
confidence: 99%